2013
DOI: 10.4103/0971-6866.124366
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of estrogen receptor alpha and catechol-O-methyltransferase genes in Turkish patients with familial prostate carcinoma

Abstract: OBJECTIVES:Estrogen is one of the most crucial hormones participating in the proliferation and carcinogenesis of the prostate glands. Genetic polymorphisms in the estrogen metabolism pathway might be involved in the risk of prostate carcinoma development. We evaluated the association between genetic polymorphisms in estrogen receptor alpha (ESR1) and catechol-O-methyltransferase (COMT) genes and the risk of developing familial prostate carcinoma.MATERIALS AND METHODS:In this study, 34 cases with prostate carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Among these eligible studies, 4 were about bladder cancer (28-31), 9 about prostate cancer (8,17,19,(32)(33)(34)(35)(36)(37) and 1 about renal cell cancer (16). Except for 1 study with a mixed population (35), 7 studies included subjects that were Caucasian (17, 28-31, 33, 34) and 6 included Asian subjects (8,16,19,32,36,37).…”
Section: Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these eligible studies, 4 were about bladder cancer (28-31), 9 about prostate cancer (8,17,19,(32)(33)(34)(35)(36)(37) and 1 about renal cell cancer (16). Except for 1 study with a mixed population (35), 7 studies included subjects that were Caucasian (17, 28-31, 33, 34) and 6 included Asian subjects (8,16,19,32,36,37).…”
Section: Eligible Studiesmentioning
confidence: 99%
“…They also identified a significant association between the COMT gene and renal cell carcinoma (16). However, the conclusions were controversial (17). On the basis of recent studies on the functions of the COMT gene and the inconsistent results obtained so far, this meta-analysis was conducted to investigate the association between cancer susceptibility and COMT Val158Met in different genetic models.…”
Section: Introductionmentioning
confidence: 99%
“…Years of publications ranged from 2001 to 2015. Genotype frequencies among controls were consistent with the HWE test, except for three studies 11,24,26. STREGA scores ranged from 29 to 36, which suggested that all of these studies were qualified to the quantitative synthesis.…”
Section: Resultsmentioning
confidence: 79%
“…In eleven included studies, the smallest case sample size was 34 (Pazarbasi et al, 2013) and largest sample size was 1034 (Cussenot et al, 2007). Total cases and controls were 3,381 and 3,276 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In total cases, genotype percentage of GG, AG and AA was 34.13%, 49.01% and 16.86% respectively (Table 1). These studies were performed in different countries-France (Cussenot et al, 2007), Iran (Omrani et al, 2009), Japan (Suzuki et al, 2003(Suzuki et al, ,2007Tanaka et al, 2006), Turkey (Pazarbasi et al, 2013), UK (Low et al, 2006), USA (Nock et al,2006;Brureau et al, 2016;Tang et al, 2017) Meta-analysis: (Table 2).…”
Section: Resultsmentioning
confidence: 99%